The Effect of Work Discipline, Motivation and Career Development on Employee Performance - Wien Dyahrini; Deden Novan Setiawan Nugraha (IKIP Mataram, 2022)
The importance of the role of human resources as the company's main asset, namely in implementing company policies and operational activities. Employees who have high performance will be the driving force in achieving company goals. This shows that employee performance must be considered in order to be skilled and responsible for the tasks given. Referring to work discipline which is suspected to be one of the factors that affect employee performance, it will greatly affect the work provided by employees at the agency. Work motivation that is not liked by employees will cause employee performance to decrease, while another determining factor is also work motivation, giving motivation can cause enthusiasm to produce better work. On the other hand, a factor that is no less important is career development, giving this reward will be able to encourage employees to be more positive at work and will be able to improve employee performance. This study aims to analyse the effect of work discipline, work motivation, and career development on employee performance. at PT SPM West Java Province. The research method uses descriptive and verification, data collection techniques through questionnaires. The research sample was 97 respondents, the sampling method used saturated sampling. From the results of the research conducted, it shows that work discipline, work motivation, and career development have a significant effect on employee performance by 49.74% which is almost close to half of the total influence, and needs to be maintained, and even in the future, it can be improved to be even better than what has been achieved at this time. a. Working hours according to predetermined SOPs are more disciplined and further improve the function of the organizational structure in accordance with their respective positions. Every morning before office hours, the company holds a debriefing to increase the intensity of communication between management and employees.